Quantificação de rádio em água pela técnica de fluorescência de raios X por reflexão total simulada por Monte Carlo - Hermógenes, Gustavo (2022)
Radium (Ra) is a naturally occurrent radioactive element and its dispersion on the environment is related also to extraction activities like in mining and oil industry. When ingested, by water or food, radium tends to accumulate in bones, increasing the risk in developing degenerative diseases associated with radiation exposure, like ostesarcomas. Due to its potencial hazardous effects to human health, international entities like World Health Organization established guidelines for the maximum contaminant levels of Ra in water. The current techniques for determination of these levels reach high sensitivity and low detection limits, but they are associated to highly complex and time consuming preparation and mesurement methods. Total Reflection X-ray Fluorescence (TXRF) Spectroscopy is a well stablished multi-elemental analysis technique for determination of trace elements in various types of samples. The purpose of this work was to propose the use of this technique, with X-ray tubes, for the determination of Ra in water. The study was carried out by Monte Carlo simulations, using the Monte Carlo N-Particle (MCNP) code. A TXRF sistem, equipped with a molybdenum X-ray tube and a SDD detector, was modelled and spectra of samples containing Ra, based on the standart reference material SRM4967A, were simulated. An experimental TXRF measurement of a ultra-pure water sample was performed for comparison with the simulated spectra. Gallium (Ga) was used as internal standart in the simulations and in the experiment. Specifically purposes in this work were to evaluate MCNP capability in modelling and simulating TXRF systems and its application domain, to obtain a Ra mass calibration curve in relation to Ga, and to determine Ra detection and quantification limits of the simulated sistem to evaluate the aplicability conditions of the proposed technique. According to the results, the system modelled with MCNP was able to reproduce typical TXRF systems characteristics, the simulations reproduced the experimental data for the ultra-pure water sample mesurement, regarding to the internal standart, and may be used for quantitative analysis relating to near fluorescence peaks’ net counts. The calibration curve was obtained based on the standart samples simulations and was able to recover the simulated arbitrary sample mass. The obtained detection and quantification limits can be achieved by current reported systems equipped with X-ray tubes. To attain international guidelines, evaporation as a pre-treatment method and the aquisition time were explored, hence the obtained limits reach the equivalent masses of the guidelines for the most naturally abundant radioisotope, 226Ra. Therefore, the simulations showthat TXRF technique, with X-ray tubes, may be used as a quick and routine check for detemination of Ra in water bodies.